(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Electrical injuries are one of the major causes of accidental deaths especially in the developing countries. This retrospective study of fatal cases of electrical burns was conducted at the Department of Forensic Medicine & Toxicology, J.N. Medical College, Belgaum, Karnataka, between 01-01-2003 to 31-12-2009. During this period total of 52 deaths due to electrical burns were autopsied and all the fatal cases were accidental. Maximum number of cases occurred during summer (65.5%). Males (84.6%) were more frequently involved and maximum number of victims were in the age group 31-40 years (28.8%). Majority of the victims were electricians (42.3%) and deaths due to low voltage electrical current (71.1%) were more than high voltage current (28.9%). The commonest cause of death was cardiac arrest (61.5%). Though electrical burns represent only a small proportion of burn injuries, the incidence of mortality, complications and disability is high. Electrical injuries can be prevented by proper safety precautions and educational programmes designed to suit the community.